"From my phone, I could rule the world": Critical engagement with maternal vaccine information, vaccine confidence builders and post-Zika outbreak rumours in Brazil. Issue 33 (30th July 2021) - Simas, Clarissa; Paterson, Pauline; Lees, Shelley; J. Larson, Heidi
Abstract: Maternal immunization is key to protecting maternal and newborn health. We interviewed pregnant women in Brazil to identify barriers to and enablers of maternal immunization in the country. In-depth interviews and focus groups were conducted in Brazil with 60 pregnant women from São Paulo and Rio de Janeiro at different stages of their pregnancies. Participants were encouraged to discuss views on safety, efficacy and importance of maternal vaccines, access to vaccines, interactions with healthcare professionals, and sources of information on vaccine-related matters. There was generally a positive regard for maternal immunization among the interviewed women, many of whom associated vaccination with protection of their unborn child. The interviewees cited several reasons for adherence to immunization guidelines, including recommendations from healthcare professionals, targeted communication campaigns, and active use of a vaccination card or booklet. There were no reported barriers for maternal vaccines. Some women using private healthcare services reported not having been asked about vaccines at check-ups, which could adversely affect vaccination rates. A rumour that vaccines caused microcephaly which emerged during the Zika outbreak was the most commonly cited reason for choosing not to vaccinate among the interviewees. This study identified important vaccine confidence builders. Many of the interviewees critically reflected upon information received, placing themselves as the decision makers over their health choices. A prominent barrier to maternal immunization was a rumour linking vaccines to microcephaly. To the best of our knowledge, this has not been previously reported in the literature and requires further investigation into the extent of this issue and how it can be mitigated.